METHODS FOR THE DETECTION OF INTERNAL DISEASES - Muminov Ravshan Davranovich (Journals Park Publishing, 2024)
The abstract should provide a concise summary of the article, including the significance of accurate detection methods in diagnosing internal diseases and an overview of the methods discussed.
Keywords: internal diseases, interrogatio, inspectio, palpatio, percussion, auscultation, cardiovascular system, breathing, digestive organs, blood, metabolism, liver, kidney.